Immune-checkpoint inhibitor-associated diabetes compared to other diabetes types - A prospective, matched control study - Tittel, Sascha R.; Laubner, Katharina; Schmid, Sebastian M.; Kress, Stefan; Merger, Sigrun; Karges, Wolfram; Wosch, Frank J.; Altmeier, Marcus; Pavel, Marianne Ellen; Holl, Reinhard W. (Journal of Diabetes, 2021)
Background To describe checkpoint inhibitor-induced diabetes mellitus (CPI-DM) and to compare with regular type 1 (T1DM), type 2 (T2DM), and medication-induced diabetes mellitus (MI-DM). Methods We included 88 177 adult patients from the Diabetes Patient Follow-Up (DPV) registry with diabetes manifestation between 2011 and 2020. Inclusion criteria were T1DM, T2DM, MI-DM, or CPI-DM. Because of the heterogeneity between the groups, we matched patients by age, sex, and diabetes duration using propensity scores. Patient data were aggregated in the respective first documented treatment year. Results The matched cohort consisted of 24 164 patients; T1DM: 29, T2DM: 24000, MI-DM: 120, CPI-DM: 15 patients. Median age at manifestation of CPI-DM patients was 63.6 (57.2-72.8) years (53.3% male). Body mass index in CPI-DM patients was significantly lower (26.8 [23.9-28.1] kg/m(2)) compared with T2DM patients (29.8 [26.2-34.3] kg/m(2), P = 0.02). At manifestation, HbA1c was significantly higher in CPI-DM compared with MI-DM, but there was no difference during follow-up. Diabetic ketoacidosis (DKA) was documented in six CPI-DM patients (T1DM: 0%, T2DM: 0.4%, MI-DM: 0.0%). Fourteen CPI-DM patients were treated with insulin, and three received additional oral antidiabetics. The most common therapy in T2DM was lifestyle modification (38.8%), insulin in MI-DM (52.5%). Concomitant autoimmune thyroid disease was present in four CPI-DM patients (T1DM: 0.0%, T2DM: 1.0%, MI-DM: 0.8%). Conclusions The data from this controlled study show that CPI-DM is characterized by a high prevalence of DKA, autoimmune comorbidity, and metabolic decompensation at onset. Structured diagnostic monitoring is warranted to prevent DKA and other acute endocrine complications in CPI-treated patients.
CRIS-Team WoS Importer:2021-08-13